Propuesta de un modelo organizacional para una empresa agrícola bananera en la zona de el Triunfo. - López Alvear, Idalia Yadira (2013)
This research was conducted at the farm enterprise " María Auxiliadora " is dedicated to the production and marketing of bananas, owned by Dr. Roberto Jalil Loor. It is located on the road El Triunfo - Bucay at Km 5.3 of the province of Guayas. This study was conducted by the technical skills - administrative having the farmer when investing or producing on the field. The main objective of this research was to recognize the shortcomings of the banana farmer in the Admin - Organizational and establish an organizational model. Obtaining the results of this investigation was through direct research, administrative staff Survey Company. It was established that the banana farm enterprise " María Auxiliadora " is a company with an area of 110 hectares, the organizational does not have a development plan that demarcates an organizational structure, functional organic manual and delegation of responsibilities of staff that makes up the human talent of the company to achieve operational and administrative excellence. It is recommended to establish an organizational structure - functional for the banana farm enterprise "María Auxiliadora", thus establishing hierarchies and responsibilities of each job. Also make future organic production because it has an efficient certification. The proposal for an organizational model for a banana farm, fruit of an arduous task of having shared experiences and experiences with administrative staff of the farm was developed.